Ipsilateral plaques display higher T1 signals than contralateral plaques in recently symptomatic patients with bilateral carotid intraplaque hemorrhage. (February 2017) - Wang, Xianling; Sun, Jie; Zhao, Xihai; Hippe, Daniel S.; Hatsukami, Thomas S.; Liu, Jin; Li, Rui; Canton, Gador; Song, Yan; Yuan, Chun; ,
Abstract: Background and aims: Prospective studies have shown a strong association between carotid intraplaque hemorrhage (IPH), detected by magnetic resonance imaging (MRI), and cerebrovascular ischemic events. However, IPH is also observed in a substantial number of asymptomatic patients. We hypothesized that there are differences in the characteristics of IPH+ plaques associated with recent symptoms, compared to IPH+ plaques not associated with recent symptoms. Methods: Patients with recent (≤2 weeks) anterior circulation ischemic events were scanned using a standardized multisequence protocol. Those showing IPH bilaterally were included and analyzed for differences in T1/T2 signals, plaque morphology, and coexisting plaque characteristics between the ipsilateral symptomatic and contralateral asymptomatic sides. Results: Thirty-one subjects (67 ± 9 years, 97% males) with bilateral IPH were studied. Despite comparable luminal stenosis (53 ± 42% vs. 53 ± 39%, p  = 0.99), T1 signal of IPH measured as signal-intensity-ratio compared to muscle was stronger (SIRIPH-to-muscle : 5.8 ± 2.4 vs. 4.7 ± 1.8, p  = 0.004) and tended to be more extensively distributed (IPH volume: 150 ± 199 vs. 88 ± 106 mm 3, p  = 0.071) on the symptomatic side. IPH+ plaques on the symptomatic side were longer (24 ± 6 vs. 21 ± 7 mm, p  = 0.026) and associated with larger necrotic core volume (406 ± 354 vs. 291 ± 293 mm 3, p  = 0.039) than those on the asymptomatic side. Conclusions: In recently symptomatic patients with bilateral carotid IPH, the symptomatic side showed stronger T1 signals, larger necrotic cores, and longer plaque length than the asymptomatic side. Serial studies on the temporal relationship between these imaging features and clinical events will eventually establish their diagnostic and prognostic value beyond the mere presence of IPH. Highlights: Intraplaque hemorrhage plaques ipsi- and contralateral to clinical event are compared. T1 signal of intraplaque hemorrhage is stronger on the symptomatic side. Plaque length and lipid core size are greater on the symptomatic side. Bilateral T1 signals are correlated, which may be influenced by systemic factors.